Fabrication of EVA connected 3D BN network for enhancing the thermal conductivity of epoxy composites. (1st November 2021) - Cui, Yexiang; Bao, Di; Xu, Fei; Gao, Yueyang; Zhang, Xiguang; Geng, Haolei; Zhou, Yixi; Zhu, Yanji; Wang, Huaiyuan
Abstract: Highly thermo-conductive polymer-based composites have attracted extensive attention in the field of electronic and heat exchange. However, it is still challenging to obtain a favorable thermal conductivity enhancement at low filler loading by directly using commercial fillers. Here, a lightweight and mechanically strong 3D hexagonal boron nitride (BN) network is prepared using BN as basic assembly unit. The prepared 3D framework displays a sponge-like structure in which the BN microplates act as a skeleton and poly (ethylene-co-vinyl acetate) (EVA) act as adhesive. Afterward, epoxy resin is then infiltrated into the 3D BN skeleton to manufacture the composites with the assistance of vacuum planetary stirring. High thermal conductivity of 1.85 W m −1 K −1 is achieved at low BN loading of 16.8 vol%, which is equivalent to a thermal conductivity enhancement of 820% in comparison with pure epoxy resin. The prepared epoxy composites possess excellent thermal management capabilities, showing large potential applications in advanced electronic devices.